Organizational Performance Index (OPI) Handbook: A practical guide to the OPI tool for practitioners and development professionals - and Pact (Pact, 2015)
This handbook is intended to help development practitioners understand how to use and what can be achieved by Pact’s Organizational Performance Index (OPI) tool. This document will provide practitioners and managers with information on how the Pact OPI works and how best to incorporate it in their country strategy or program.